2019
DOI: 10.1038/s41598-019-45187-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong coupling probed by Coherent Population Transfer

Abstract: Light-matter interaction, and the understanding of the fundamental physics behind, is the scenario of emerging quantum technologies. Solid state devices allow the exploration of new regimes where ultrastrong coupling strengths are comparable to subsystem energies, and new exotic phenomena like quantum phase transitions and ground-state entanglement occur. While experiments so far provided only spectroscopic evidence of ultrastrong coupling, we propose a new dynamical protocol for detecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…In the last few years a new ultrastrong coupling (USC) regime, where light-matter coupling is large enough to break the rotating wave approximation (RWA), has been achieved in cavity and circuit QED, THz metamaterials, intersubband polaritons and other physical systems [7,8], and has been subject of extensive theoretical analysis [7][8][9][10][11][12][13][14] showing thatnovel and outstanding physics arises in this non-perturbative regime. In very recent work it has been shown that USC can be a powerful tool for the generation of photon pairs from entangled states in optomechanical systems [15] and circuit-QED architectures [16]. New results on the dynamics of photons are here reported.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the last few years a new ultrastrong coupling (USC) regime, where light-matter coupling is large enough to break the rotating wave approximation (RWA), has been achieved in cavity and circuit QED, THz metamaterials, intersubband polaritons and other physical systems [7,8], and has been subject of extensive theoretical analysis [7][8][9][10][11][12][13][14] showing thatnovel and outstanding physics arises in this non-perturbative regime. In very recent work it has been shown that USC can be a powerful tool for the generation of photon pairs from entangled states in optomechanical systems [15] and circuit-QED architectures [16]. New results on the dynamics of photons are here reported.…”
Section: Introductionmentioning
confidence: 73%
“…STIRAP in superconducting nanocrcuits has been studied theoretically [27][28][29] and experimentally [30,31] since it can be used for new type of quantum gates [32] possibly resilient to solid state quantum noise [33][34][35][36][37][38]. In the USC scenario STIRAP can be used to detect virtual photons in the dressed eigenstates of the system, by coherently amplifying their conversion to real photons [16,24,25]. We consider a three-level atom (basis {|u , |g , |e }) ultrastrongly coupled to a single light mode of frequency ω c , resonant with the e.gtransition energy ε, described by the Hamiltonian…”
Section: Generation Of Two-photon Pairs By Stirapmentioning
confidence: 99%
See 1 more Smart Citation
“…Those virtual photons, localised in proximity of the quantum emitter [10,11], can become real and be radiated when the system parameters are modulated in time [12][13][14][15][16][17], an effect reminiscent of the Dynamical Casimir effect [18]. Notwithstanding a remarkable interest, both theoretical [19][20][21][22] and experimental [23][24][25][26][27][28][29] in the physics and phe-nomenology of the ultrastrong coupling regime, for the moment no direct evidence of the virtual photons has been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spectroscopy of ancillary qubits has been proposed in [33] to probe the ground states of ultrastrongly-coupled systems. Moreover, methods alternative to the analysis of the transmission spectra have been recently devised to probe the USC regime [34,35]. The dissipative Rabi model which describes our setup can be mapped to a SBM where the spin interacts directly with a bosonic bath characterized by an effective spectral density function peaked at the oscillator frequency [36], which constitutes a so-called structured environment.…”
mentioning
confidence: 99%